Aplysin induces apoptosis in glioma cells through HSP90/AKT pathway. (May 2015) - Gong, An-jing; Gong, Li-li; Yao, Wei-cheng; Ge, Na; Lu, Lu-xiang; Liang, Hui
Glioma is one of the most common malignancies in the world. However, an effective regiment is lacking. Increasing evidence indicated that PI3K/AKT signaling is critical for the survival of glioma. In this study, we aimed to study the effect of aplysin on the survival and proliferation of GL26 glioma cells and the involved mechanisms. The data showed that aplysin suppressed the viability of glioma cells in both dose- and time-dependent manners. It also induced G0 /G1 arrest and apoptosis in glioma cells. Western blot assays revealed that aplysin treatment changed p-AKT expression by impairing the formation of Heat shock protein 90/AKT complex. Aplysin significantly increased the survival time of mice-bearing glioma and reduced the weights of the established gliomas. Collectively, aplysin can inhibit the proliferation of GL26 glioma cells and induce apoptosis in vitro, perhaps through suppressing PI3K/AKT pathway. It can also inhibit glioma growth in vivo and prolong the survival of mice. Thus, aplysin may be a novel therapeutic drug for glioma.